EVALUASI KEGIATAN PELAYANAN PENDAFTARAN PASIEN DI RS X MALANG - Chyntia Vicky Alvionita; Elystia Vidia Marselina (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2024)
The registration service is the first service and directly interacts with the patient and the place where they will register at the polyclinic they are going to. Observational data has revealed that a number of issues, including SIMRS and the network, continue to impede patient registration services. Evaluating patient registration service activities is one approach taken to address this issue. The aim of this research is to evaluate activities in patient registration services. The instrument used was an interview sheet. This type of research uses qualitative descriptive analysis to describe the results of evaluation of patient registration services. The study's findings indicate that although RS X Malang's registration service is functioning effectively, a number of issues continue to arise. Patient registration is frequently hampered by sluggish and unreliable internet connections. Delays in the registration procedure are possible, and SIMRS disruptions happen frequently. In addition, the tracer is still manual, which increases the possibility that the registration officer will overlook recording the patient's medical record information. Another issue is that there is currently no bridging between SIMRS and BPJS, which makes BPJS patient registration more time-consuming due to its multiple steps.